The Inhibitory Role of Di-2-ethylhexyl Phthalate on Osteogenic Differentiation of Mesenchymal Stem Cells Via Down-regulation of RUNX2 and Membrane Function Impairment - Abnosi, Mohammad Hossein; Aliyari Babolghani, Zahra (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Blood contamination of di-2-ethyl hexyl phthalate (DEHP) has been reported due to its release following medical procedures such as blood transfusion and vital liquid injection. We investigated the effect of DEHP on osteogenic differentiation of mesenchymal stem cells and their viability. Methods: The rat bone marrow mesenchymal cells (MSCs) were cultured three times, and the third passage kept in the differentiation medium with the presence of DEHP. The viability of differentiated cells, sodium and potassium level, calcium concentration, total protein concentration, and the activity of lactate dehydrogenase, alkaline phosphatase, alanine transaminase, and aspartate transaminase were determined. Also, the concentration of malondialdehyde, total antioxidant capacity, the activity of superoxide dismutase and catalase were estimated. Finally, the level of matrix deposition and expression of alkaline phosphatase (ALP) and runt-related transcription factor 2 (RUNX2) genes were evaluated. Results: We observed a concentration-dependent and significant reduction of matrix mineralization based on alizarin red and calcium analysis. Besides, the expression of ALP and RUNX2 gene was down-regulated, and alkaline-phosphatase activity reduced significantly. Also, we observed cell viability reduction but the elevation of lactate dehydrogenase activity and malondialdehyde level. Sodium level was elevated too, whereas the activity of transaminases, oxidative stress enzymes, potassium level, and total antioxidants decreased. Conclusion: DEHP contamination reduced matrix mineralization due to the down-regulation of the genes involved in osteogenic differentiation and viability reduction via electrolyte and metabolic imbalance as well as induction of oxidative stress.